Numerical and experimental investigation on seismically damaged reinforced concrete wall panels retrofitted with FRP composites. (January 2015) - Todut, C.; Dan, D.; Stoian, V.
Abstract: This paper presents the results of an experimental program on precast reinforced concrete wall panels (PRCWP). These panels were damaged under cyclic lateral loads and thereafter retrofitted or rehabilitated and retested. The experimental program was conceived to analyse the possibilities of using FRP materials for strengthening the PRCWP affected by seismic action. The fibre reinforced polymer (FRP) composites are frequently used in strengthening structural elements because of their superior characteristics and simple technology. The existing literature lacks information concerning reinforced concrete walls (RC) retrofitted by FRP composites compared to other structural members. This paper presents various effective strengthening solutions that can be applied to damaged elements. The retrofitting solutions consist in use of EBR-CFRP strips, combined EBR-CFRP strips with NSM-CFRP plates, textile reinforced mortar (TRM) using glass fibre grid, and TRM using carbon fibre grid. The solutions were proposed with the aim of restoring the wall shear resistance and to provide the confinement effect at the ends. The experimental results indicate that the performance of the elements, repaired and strengthened, were almost equal to or higher than the reference elements in terms of load bearing capacity, stiffness and energy dissipation capacity. A more ductile behaviour compared to the reference elements was recorded for the rehabilitated and retrofitted elements.